Determination of Natural and Artificial Radionuclides in Hot Water Spring Mud of Haymana-Ankara Spa (Turkey) - Köse, A.; Varinlioğlu, Ahmet; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Asian Journal Of Chemistry, 11/100 Rajendra Nagar, Sector 3,, Sahibabad 201 005, Ghaziabad, india, 2010)
gamma-Ray spectrometric analysis was performed on hot water spring mud samples, collected from Haymana-Ankara (Turkey) Spa, a well known health resort in the middle of Anatolia. The contents of natural and artificial radionuclides (Ra-226, U-235, U-238, Th-228, Th-232, K-40 and Cs-137) were determined. The results were compared with the radioactivity values of different Spas. gamma-Isotopic analysis indicated that the maximum level concentration of the thermal mud samples for Ra-226, U-235, U-238, Th-228, Th-232, K-40 and Cs-137 were (Bq/kg) 162, 7.4, 156, 75, 127, 66 and 1.6, respectively.
Keywords: gamma-Isotopic analysis; Mud; Radionuclides; Spa; radioactivity; gama-izotopik analiz; çamur; radyonuklitler; radyoaktivite